GAMBARAN TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI TENTANG KESEHATAN MENSTRUASI PADA REMAJA AWAL YANG TINGGAL DI ASRAMA NUSANTARA - Retnowuni, Arifa (Universitas Pesantren Tinggi Darul Ulum, 2018)
Teenagers aged 12-15 years usually experience menstruation. This condition usually occurs once a month. Usually the menstrual period is between 3-7 days. During menstruation, you will usually experience mood changes caused by hormonal changes in a person's body and this happens during menstruation. Young women who first experience menstruation mostly feel worried and feel uncomfortable when they come to their months, thus limiting their activities. In addition, a long menstrual cycle scares because of bleeding. Knowledge of menstruation, menstrual cycle, and menstrual disorders experienced is very important for young women. The purpose of this study is to determine the level of reproductive health knowledge about menstrual health in early adolescents who live in boarding schools. this study uses pure descriptive, the sampling technique using purposive sampling. And data analysis using frequency distribution using SPSS 15 software. The instrument used is a questionnaire to measure the level of knowledge of adolescents who have been validated. Based on respondents' data from the level of knowledge about understanding menstruation as much as 41% (23 people) had a good level of knowledge, 18 people (32%) had sufficient knowledge and the remaining 26.8% (15 people) had less knowledge. While seen from the level of knowledge related to the menstrual cycle, most respondents had less knowledge about the menstrual cycle as much as 42.8% (24 people) and as many as 25% (14 people) had a good level of knowledge. Furthermore, based on the level of knowledge of respondents to menstrual disorders, most are still lacking as much as 46.4% (26 people) and the remaining 14 people (25%) have a sufficient level of knowledge of menstrual disorders Keywords: Health, menstruation, reproduction, adolescence.